NOTARY'S OBLIGATION TO ATTACH SUSPICIOUS FINANCIAL TRANSACTIONS AS A FORM OF MONEY LAUNDERING - Amalia Destyna Chusmayanti; Budi Parmono; Sunardi Sunardi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The involvement of Notaries as public officials in money laundering practices is one of the methods used by criminals to disguise the origin of funds from criminal acts, such as corruption. Notaries are often used to prepare deeds of establishment of legal entities or purchase assets to obscure these illegal transactions. This research elucidates the duties borne by Notaries in conveying indications of atypical financial activities as an instrument for deterring money-laundering offenses. The issues examined encompass: (1) the normative framework governing the obligations and accountability of Notaries in submitting reports on anomalous financial dealings; (2) the delineation of criteria for such transactions that necessitate disclosure; and (3) the juridical repercussions imposed when Notaries neglect to report. The study employs a normative juridical method through a statutory and regulatory approach. Its findings reveal that the mandate to report is anchored in multiple legal instruments, including Law Number 8 of 2010 on the Prevention and Eradication of Money Laundering, the Notary Law, Minister of Law and Human Rights Regulation No. 9 of 2017, and PPATK Regulation No. 6 of 2021. The parameters for identifying suspicious financial transactions are articulated in Article 1 point 8 and Article 8 of Government Regulation Number 43 of 2015. When a Notary fails to submit such reports, they may incur administrative penalties as prescribed in Minister of Law and Human Rights Regulation No. 61 of 2016 and the Notary Law.